Self-Efficacy and Mental Health of Mothers with Infants 0-6 Months on Breastfeeding Status: A Comparative Study - Pratiwi, Bintang Agustina; Kartini, Apoina; Jati, Sutopo Patria; Sriatmi, Ayun (IJNP (Indonesian Journal of Nursing Practices), 2024)
Background: Exclusive breastfeeding coverage in Bengkulu City has decreased over the last three years. Mothers' confidence in their abilities and good mental health become an essential part of supporting exclusive breastfeeding.Objective: This study aims to examine the differences between self-efficacy and mental health of mothers based on their breastfeeding status, located in Bengkulu City.Methods: The researchers employed a cross-sectional approach to analyze the study. The sample consisted of 72 mothers with infants aged 0-6 months. The researchers selected the samples using a purposive sampling technique. Data collection was carried out using a digital questionnaire (via Google Forms) through validity and reliability tests. Data were analyzed using an independent t-test. The mean self-efficacy score of partially breastfeeding mothers is lower than that of exclusively breastfeeding mothers. The mean mental health score of partially breastfeeding mothers is higher than that of exclusively breastfeeding mothers.Results: The results of the independent t-test found that the average self-efficacy score of exclusively breastfeeding mothers was 55.58, and the average mental health score of partially breastfeeding mothers was 10.32.Conclusion: There was a difference in the self-efficacy and mental health scores of partially and exclusively breastfeeding mothers. A high self-efficacy score indicates high maternal confidence. Meanwhile, high mental health scores indicate that mothers experience symptoms of psychological disorders. The achievement of successful exclusive breastfeeding is closely related to boosting self-assurance and preserving a mother's mental well-being.